Study on the damping capacity of a fluidic baffle under different injection conditions. (October 2019) - Song, Wooseok; Lee, Jongkwon; Koo, Jaye
Abstract: Passive control methods have been widely used to decrease the intensity of combustion instability, and a structural baffle injector has been applied in liquid rocket-engine development. However, the development cost of a structural baffle injector increases because the thrust of a liquid rocket engine should increase as the weight increases. The objective of this paper is to analyze the damping capacity of a fluidic baffle injector using a dissimilar injector arrangement. In this study, a cold-flow test was conducted to observe the effect of using a fluidic baffle injector, and a pulse gun was adopted to generate the pressure wave. A gas-centered swirl coaxial injector and a shear coaxial injector were used to inject the bipropellant. Gaseous nitrogen and liquid water were used for the bipropellant. In addition, multi injectors and a pulse gun were used to compare the effects of a gas-centered swirl coaxial injector and a shear coaxial injector, each acting as the fluidic baffle, on the spray intensity under different conditions. When the gas-centered swirl coaxial injector was used as the fluidic baffle injector, the amplitude increase rate increased as the momentum flux ratio decreased. However, the shear coaxial injector obstructed the pressure-wave propagation. Therefore, the shear coaxial injector was a better fluidic baffle injector than the gas-centered swirl coaxial injector. Highlights: This study proposes a fluidic baffle injector to prevent pressure wave. Pressure wave penetrates all injection zones in the case of weak jet stream. A low momentum flux ratio of jet stream could not prevent pressure wave propagation. Shear coaxial injector was a better fluidic baffle than swirl coaxial injector.